2009
DOI: 10.1080/01639620802296360
|View full text |Cite
|
Sign up to set email alerts
|

How Close Is Too Close? Balancing Closeness And Detachment In Qualitative Research

Abstract: Conducting qualitative research among deviant or criminal populations can be daunting, especially when one considers the ambiguities and complexities that often plague such research. A particularly challenging issue that many qualitative researchers face is handling the tensions experienced when trying to assess and achieve the appropriate levels of intimacy or closeness (i.e., developing rapport with subjects and becoming a trusted presence in their lives and social worlds) and detachment (i.e., being able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…But just as a mirror held too close to its subject might see the details but miss the bigger picture, so those engaged in shadowing need to find the balance between ‘sympathetic proximity’ and ‘critical distance’ if they are to provide analytic insight. But if we remain critically self-conscious of our positionality (Maier and Monahan, 2010) and priorities during this process, we can still retain sight of our research questions without ‘going native’ or allowing our closeness to compromise scholarly standards. Thus the notion of critical proximity is perhaps a way out of the impasse, where it recognizes the need to be self-aware and reflexive, but also sympathetically and fully engaged in the process of understanding the world of another.…”
Section: Methodological Reflectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…But just as a mirror held too close to its subject might see the details but miss the bigger picture, so those engaged in shadowing need to find the balance between ‘sympathetic proximity’ and ‘critical distance’ if they are to provide analytic insight. But if we remain critically self-conscious of our positionality (Maier and Monahan, 2010) and priorities during this process, we can still retain sight of our research questions without ‘going native’ or allowing our closeness to compromise scholarly standards. Thus the notion of critical proximity is perhaps a way out of the impasse, where it recognizes the need to be self-aware and reflexive, but also sympathetically and fully engaged in the process of understanding the world of another.…”
Section: Methodological Reflectionsmentioning
confidence: 99%
“…Many classic ethnographic studies have been based upon the work of researchers who proactively involve themselves in the actual work, roles, or vocation of those they are researching, whether this is working on an Icelandic dairy farm (Hastrup, 1995), becoming involved in the training programme in an accountancy office (Coffey, 1999), or living with Benedictine monks in Florida (Angrosino and Mays de Perez, 2000). In these cases, researchers have become to some extent ‘members’ or at least ‘honorary’ members of a particular group for a time (Adler and Adler, 1987; Angrosino and Mays de Perez, 2000; Dewalt and Dewalt, 2002), and various responsibilities might be accorded to them as a condition of access, some of which might cross legal boundaries in the case of research into deviance (Maier and Monahan, 2010). In contrast, for those engaged in shadowing, even over a relatively long period of time, it may be inappropriate or impossible to take on any kind of active ‘membership’ role.…”
Section: Shadowing As Research Strategymentioning
confidence: 99%
“…This leaves less experienced ethnographers in particular potentially unprepared to manage questions of 'how close is too close?' (Maier & Monahan 2010), as we illustrated through describing our own research process.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative researchers engaged in social health studies have reported a range of forms of personal engagement with participants. This has included spending extended time among the population being studied, witnessing what some might refer to as deviant behavior, and being asked to run errands for participants (Maier & Monahan, 2010). In longitudinal studies or research that includes a number of interviews with the same group of participants, this involvement can often include sharing social occasions and the sending of christmas cards and other similar social interactions.…”
Section: Reflexivity and Ethical Mindfulness In Actionmentioning
confidence: 99%